Experimental Subarachnoid Hemorrhage Drives Catecholamine-Dependent Cardiac and Peripheral Microvascular Dysfunction - Dinh, Danny D.; Lidington, Darcy; Kroetsch, Jeffrey T.; Ng, Chloe; Zhang, Hangjun; Nedospasov, Sergei A.; Heximer, Scott P.; Bolz, Steffen-Sebastian (Frontiers in Physiology, 2020)
Subarachnoid hemorrhage (SAH) is a devastating cerebral event caused by an aneurysmal rupture. In addition to neurological injury, SAH has significant effects on cardiac function and the peripheral microcirculation. Since these peripheral complications may exacerbate brain injury, the prevention and management of these peripheral effects are important for improving the overall clinical outcome after SAH. In this investigation, we examined the effects of SAH on cardiac function and vascular reactivity in a well-characterized blood injection model of SAH. Standard echocardiographic and blood pressure measurement procedures were utilized to assess cardiac function and hemodynamic parameters in vivo; we utilized a pressure myography approach to assess vascular reactivity in cremaster skeletal muscle resistance arteries ex vivo. We observed that elevated catecholamine levels in SAH stun the myocardium, reduce cardiac output and augment myogenic vasoconstriction in isolated cremaster arteries. These cardiac and vascular effects are driven by beta- and alpha-adrenergic receptor signaling, respectively. Clinically utilized adrenergic receptor antagonists can prevent cardiac injury and normalize vascular function. With respect to the latter, beyond alpha adrenergic dependence, the precise mechanism augmenting peripheral vascular tone remains undefined. We found that tumor necrosis factor (TNF) gene deletion prevents the augmentation of myogenic reactivity in SAH: since membrane-bound TNF serves as a mechanosensor in the arteries assessed, alpha-adrenergic signaling putatively augments myogenic vasoconstriction by enhancing mechanosensor activity.